Durasi Cekaman Kekeringan yang Tepat untuk Induksi Bunga Jeruk Keprok Madura: Appropriate Duration of Drought Stress for Madura Tangerine Flower Induction - Rahayu, Resa Sri; Poerwanto, Roedhy; Efendi, Darda; Widodo, Winarso Drajad (Jurnal Hortikultura Indonesia, 2020)
Drought stress is one of the techniques used to induce off-season tangerines flower in an effort to meet the availability of tangerines throughout the year. The correct duration of drought stress is important to learn to avoid severe stress and obtain optimum flower yield. This study aims to determine the duration of proper drought stress to induce flowering of Madura lowland tangerine. The study was conducted in the PKHT-IPB Experimental Garden with a height of ± 300 masl from April-May 2019. Experiment was designed with Randomized Block Design (RBD) by one factor treatment, namely drought stress duration with five levels: without drought stress as control, one week drought stress duration, two weeks drought stress duration, three weeks drought stress duration and four weeks drought stress duration. The results showed that duration of drought stress affects the success of induction of Madura tangerine flowers. Drought stress duration of 2, 3 and 4 weeks with 81.81%, 65.21% and 55.39% of field capacity water content successfully induced the flowers. Flowers appear at 3, 2 and 1 week after rewatering and routine irrigating in stress duration treatment for 2, 3 and 4 weeks. Three weeks without irrigation is the optimum duration of drought stress for induction of Madura tangerine flowers.